La Slovaquie et l'Europe Essais et articles - Lipták, Ľubomír (Histoire(s), 2019)
Through a selection of essays and articles by historian Ľubomir Lipták, the book explores the history of Slovakia, a landlocked country in the heart of Central Europe, at the junction of different linguistic areas. A multicultural country until the late 1930s, Slovakia became ethnically homogenous after the Second World War. This volume, edited by Roman Krakovsky, examines these transformations. It also invites us to reflect on the role of history and the historian in the city, collective identities. In Lipták's characteristically incisive style and writing, these texts present an uncompromising approach to the transformations that Slovakia and its region have undergone over the short twentieth century. They also help us to understand its present.